Effects of maximum upper-body strength training on double poling on female skiers - Korhonen, P.; Pohjola, M.; Ohtonen, O.; Linnamo, V. (Science and Skiing VIII. Book of the 8th International Congress on Science and Skiing, 2020)
Cross-country skiing as a sport has gone through a great transformation in the past 35 years. Modern skiing equipment is mostly made of carbon fibre and other light, but strong materials. Tracks are machine prepared and track profiles homologated. There are two separate skiing styles; classic and skate skiing. Sprint skiing was introduced around 2000. All this has led to increased average speeds and evolution of skiing tecniques. Maximum oxygen uptake is still the main success factor, but upper body power output and overall strength have also become important (Sandbakk & Holmberg 2014). High muscle mass and low fat-percentage correlate with peak speed especially in double poling (Stöggl et al., 2010). Double poling has become maybe the most prolific subtechnique of modern classic skiing. Races from FIS World Cup sprints to 90 km Wasaloppet have been won by using double poling alone. At first double poling became a trend among male skiers but women soon followed. Sandbakk et al. (2014) found out that a gap in skiing performace between sexes at different skiing techniques was at its largest when portion of upper body contribution to total work was higher. Elite level female cross-country skiers were able to prolong their double poling test end time considerably after nine weeks of upper body strength training. Strength training had no effect on oxygen uptake capacity (Hoff et al., 1999). Similar findings have been made in other studies conducted on endurance athletes, as was noted by Aagaard & Anders (2010) and Beattie et al. (2015) in their reviews. However, Skattebo et al. (2016) found upper body strength training and subsequent strength gains to have no benefit for double poling on young female skiers. Their result was not in line with other studies where the subjects were older. Was the chosen strength training method (linear model, two sessions per week) not enough in terms of volume or perhaps was the testing method (double poling ergometer) not reflecting real skiing accurately? Therefore, the aim of the present study was to examine if a non-linear 8-week upper body strength training would improve double poling performance.